2011
DOI: 10.14411/fp.2011.023
|View full text |Cite
|
Sign up to set email alerts
|

Natural and anthropogenic factors shape metazoan parasite community structure in mummichog (Fundulus heteroclitus) from two estuaries in New Brunswick, Canada

Abstract: the mummichog Fundulus heteroclitus (L.) is abundant in euryhaline environments on the east coast of North America, ranging from the gulf of Mexico to the gulf of st. lawrence. it is a common prey item for several species of fishes and shorebirds, and is therefore a key component in intertidal food webs (Scott and Scott 1988). Mummichog are relatively long-lived, with a life span of up to five years, and are largely sedentary, feeding mainly on benthic invertebrates within a restricted home range. these traits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 34 publications
(22 reference statements)
1
22
0
Order By: Relevance
“…This study highlights the importance of good sample design and replication. This point is supported by other studies which showed large-scale hydrological effects on parasite communities to be more pronounced than those of contaminants [ 130 132 ]. Indeed, Marcogliese et al ([ 129 ] and references therein) suggested that parasite communities as indicators may not be sensitive enough to detect effects of low to moderate pollution or that effects may be overshadowed by those of natural environmental variation.…”
Section: Parasites As Indicators Of Ecosystem Healthsupporting
confidence: 81%
“…This study highlights the importance of good sample design and replication. This point is supported by other studies which showed large-scale hydrological effects on parasite communities to be more pronounced than those of contaminants [ 130 132 ]. Indeed, Marcogliese et al ([ 129 ] and references therein) suggested that parasite communities as indicators may not be sensitive enough to detect effects of low to moderate pollution or that effects may be overshadowed by those of natural environmental variation.…”
Section: Parasites As Indicators Of Ecosystem Healthsupporting
confidence: 81%
“…Also, myxozoan communities in spottail shiners are quite different upstream and downstream of the island of Montreal in the same river (Marcogliese et al 2009; Krause et al 2010). Similarly, based on their parasite communities, estuarine and freshwater samples of mummichogs ( Fundulus heteroclitus ) prove quite different from each other in two New Brunswick rivers (Blanar et al 2011). While the above studies do not concern commercial fishes, these species are important forage fishes and the information is certainly relevant if any fisheries employ a more comprehensive ecosystem approach or need to comprehend the resource base for a particular commercial fish species.…”
Section: What Could We Learn From Non-tagging Studies?mentioning
confidence: 99%
“…As a result of the high parasite diversity of intermediate trophic fishes -i.e., those that consume invertebrates and are prey for both predatory fishes and piscivorous birds -and the ability to estimate age and thus parasite recruitment time, juvenile fish are excellent models to investigate the potential efficiency of parasites as bioindicators for use in environmental monitoring; however, due to the time and knowledge required to sample and identify all parasites present within a host species, previous authors advocate monitoring only individual parasite taxa using prior knowledge of their biology and distribution within a system (Blanar et al, 2011). Additionally, selection of model species for habitat specific data requires that Table 1 Creek watershed land-use, water quality and benthic scores for three creeks in eastern Ontario, Canada.…”
Section: Introductionmentioning
confidence: 99%